Implementation of the TOPSIS Method for Determining Raw Material Selection at Mooi Cake Simpang IV Sipin Branch - Aldy Suryawinata; Ediansa, Oka; Akbar, Zulfikri; Santoso, Heri; Helmina Helmina (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of the culinary industry, particularly in bakery and cake shop businesses, requires companies to maintain consistent product quality while managing production costs efficiently. One important factor influencing production performance is the proper selection of raw materials. Mooi Cake Simpang IV Sipin Branch faces challenges in determining the best raw materials due to the availability of several suppliers with different characteristics, while the selection process is still conducted manually and tends to be subjective. Therefore, this study aims to apply the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method within a decision support system to support objective and structured decision making. This research uses a quantitative approach with a decision support system method. Data were collected through observation, interviews, and literature review, then analyzed using the TOPSIS method by considering six criteria, namely price, quality, delivery timeliness, raw material availability, supply consistency, and supporting criteria. The analysis stages include constructing a decision matrix, normalizing data, weighting criteria, determining positive and negative ideal solutions, calculating distances, and determining preference values and rankings. The results show that the TOPSIS method produces clear and easily understood preference values, making it easier for management to select the most suitable raw materials. Based on the results, Raw Material 2 obtained the highest preference value and is recommended as the best alternative for Mooi Cake Simpang IV Sipin Branch. The implementation of the TOPSIS method is expected to reduce subjectivity, improve decision-making effectiveness, and support operational efficiency and product quality improvement.